Determinants of ChatGPT Use and its Impact on Learning Performance: An Integrated Model of BRT and TPB - Al-Qaysi N.; Al-Emran M.; Al-Sharafi M.A.; Iranmanesh M.; Ahmad A.; Mahmoud M.A. (Taylor and Francis Ltd., 2025)
The rapid emergence of Generative Artificial Intelligence (GAI) heralds a significant shift, opening new frontiers in how education is delivered. This groundbreaking wave of technological advancement is poised to redefine traditional learning, promising to enhance the educational landscape with unprecedented levels of personalized learning and accessibility. Despite GAI?s progressive infiltration into various educational strata, limited empirical research exists on its impact on students? learning performance. Drawing on the Theory of Planned Behavior (TPB) and Behavioral Reasoning Theory (BRT), this study investigates the determinants affecting students? use of ChatGPT and its influence on learning performance. The data were collected from 357 university students and were analyzed using the PLS-SEM technique. The results supported the role of ChatGPT in positively affecting students? learning performance. In addition, the results showed that reasons for and against adoption are pivotal in shaping students? attitudes. ChatGPT use is found to be significantly affected by attitudes, subjective norms, and perceived behavioral control. Besides the theoretical contributions, the findings offer various implications for stakeholders and underscore the necessity for educational institutions to foster a conducive environment for GAI adoption, addressing ethical and technical concerns to optimize learning experiences. ? 2024 Taylor & Francis Group, LLC.